Prosedur penelitian: suatu pendekatan praktik - Suharsimi Arikunto (Rineka Cipta, 1991)
ws,c.1-4/budi, c.5/sgh c6,ws.c.7/ir,c.8/oen, c.9/ast c.10/ast c.11/ir,c.12/stoc2, c.1, c.4,c.5-6,12./stoc5.c13/ stc14=c.14/irh,c.15-17/oen.18